Mathematical modeling, simulation, visualization and e-learning : proceedings of an international workshop held at Rockefeller Foundation's Bellagio Conference Center, Milan, Italy, 2006 - Konaté, Dialla. (Springer, 2017)
This book is a collection of articles written by some of the most prominent leading applied mathematicians, as well as articles from young and promising scientists from Africa, Asia and Europe. The common objective of these articles is to present an important issue which is currently widely discussed in scientific investigation with major human, economic or ecological implications. One main feature of the series, which the current book exemplifies, is that each article is as deep as an expert lecture but is also self-contained, so that even isolated scientists with limited resources can profit greatly from it. Another feature of this book is that each article is meant to present a collection of open questions which can fuel undergraduate or graduate research activities even in smaller or more isolated scientific communities